THE DEVELOPMENT OF AUDIO VISUAL PRACTICUM GUIDE THE SUBJECT OF FLUID TO IMPROVE THE LEARNING RESULT OF THE PHYSICS OF THE COGNITIVE AND PSYCHOMOTOR ASPECTS OF STUDENTS 9 YOGYAKARTA SENIOR HIGH SCHOOL - Wahyu Elko Septiyono , Nur Kadarisman (Jurnal Pendidikan Fisika, 2018)
Abstrak Penelitian ini bertujuan untuk : 1) Mengetahui perbedaan hasil belajar ranah kognitif siswa yang menggunakan modul praktikum media audio visual dengan modul praktikum cetak pada. 2) Mengetahui perbedaan hasil belajar ranah psikomotor siswa yang menggunakan modul praktikum media audio visual dengan modul praktikum cetak.3) Mengetahui yang lebih baik antara penggunaan modul praktikum menggunakan media audio visual dengan modul praktikum media cetak ditinjau dari ranah kognitif pada pokok bahasan fluida di SMA Negeri 9 Yogyakarta. 4) Mengetahui yang lebih baik antara penggunaan modul praktikum menggunakan media audio visual dengan modul praktikum media cetak ditinjau dari ranah psikomotor. Kata kunci : panduan praktikum media audio visual, fluida, hasil belajar ranah kognitif dan psikomotor. Abstract This study aims to: 1) Know the difference in learning outcomes of the cognitive domain of students using visual media module practice module with printed lab module on. 2) Knowing the difference of psychomotor student learning result using visual media practicum module with print practice module .3) Knowing better between using practice module using audio visual media with print media practicum module viewed from the cognitive domain on the subject of fluid in SMA Negeri 9 Yogyakarta.4) Knowing better between the use of practicum module using audio visual media with print media practicum module in review from the psychomotor domain. Keyword : audio visual module practice, fluids, learning outcome cognitive domain and psychomotor domain